Зимовка птиц в Западном Крыму в 2005-2006 годах - Кучеренко, В.Н. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2007)
The communication presents data of counts, executed in November-March 2005-2006 along 6 routes in the area of Sakskiy and Chernomorskiy regions and the city of Eupatoria. Favourable weather conditions in November-December 2005 made for mass wintering of birds in the region. Since the second half of January 2006 the weather suddenly changed for the worse; this fact brought about concentration of birds near non-freezing water-bodies (Lake Kizil-Yar, Lake Donuzlav). In a total 72 bird species were recorded in the region during this period.